The Role of the Microbiota in the Diabetic Peripheral Artery Disease. (8th May 2019) - Biscetti, Federico; Nardella, Elisabetta; Cecchini, Andrea Leonardo; Landolfi, Raffaele; Flex, Andrea
Abstract : Vascular complications of diabetes mellitus represent a major public health problem. Although many steps forward have been made to define the causes and to find the best possible therapies, the problem remains crucial. In recent years, more and more evidences have defined a link between microbiota and the initiation, promotion, and evolution of atherosclerotic disease, even in the diabetic scenario. There is an urgency to develop the knowledge of modern medicine about the link between gut microbiota and its host's metabolic pathways, and it would be useful to understand and justify the interindividual diversity of clinical disease presentation of diabetic vascular complication even if an optimization of pharmacological treatment has been made or in the case of young patients where hypertension, dyslipidemia, and diabetes are not able to justify a very quick progress of atherosclerotic process. The aim of the present review is to gather all the best available evidence in this regard and to define a new role of the microbiota in this field, from biomarker to possible therapeutic target.